A configurational force based anisotropic damage model for original isotropic materials. (15th June 2019) - Yuan, Zhongbo; Li, Qun
Highlights: The damage model is constructed with material forces as internal variables. The model describes anisotropic damage evolution for original isotropic material. Anisotropy is introduced by the orientated energy potential gradient. The model is numerically implemented to indicate the directional damage growth. The model could be expanded into a combined damage and fracture theory. Abstract: In this paper, a configurational damage model is proposed to provide an efficient approach suitable for the anisotropic damage evolution at the stress concentration for initial isotropic materials. Within the framework of continuum damage mechanics, configurational forces as the damage driving forces are introduced as damage variables to describe the effective elastic properties for quasi-brittle materials. The potential energy gradient on the material space point is derived mathematically using an infinitesimal element approach. To deal with the directional damage growth, a simple constitutive equation together with the damage degradation law is constructed by introducing the concept of damage effect tensor M(ω). The calculation method of nodal configurational forces is given via the finite element method (FEM). A scheme for the implementation of the damage model in commercial FEM codes is then detailed. A series of designed experiments and numerical simulations are carried out to illustrate the validity and convenience of the configurational damage model. It is conceived that the degradation of material effective elastic properties is controlled by the configurational resultant force, which may directly identify the direction of microdefects. Also the method can be extended to the progressive fracture propagation problem including the effect of damage evolution. Because of the clear physical interpretation and vector nature of configurational forces, the proposed model can appropriately be used to predict structure anisotropic failure.